The Trajectory of Bali Democracy Forum: Indonesia’s Soft Power and Nation Branding - Anak Agung Mia Intentilia (Politicos: Jurnal Politik Dan Pemerintahan, 2025)
As one of the largest Muslim-majority countries with an emerging economy, the conversation regarding Indonesia’s democracy has always been intriguing. The path of Indonesia’s democratic values has evolved from Independence Day to the current globalization era. In addition to examining Indonesia’s domestic reforms, the contemporary issues of this country’s role in shaping the regional architecture of democracy have also expanded to the realm of international relations. In 2008, Indonesia initiated the Bali Democracy Forum (BDF) as an annual platform to promote dialogue-based cooperation and uphold the values of peace and democracy. Since its inception, the BDF has been conducted 15 times, with the latest forum held in 2023 under the theme “Democracy in a Changing World: Leadership and Solidarity.” This paper aims to explore key features of the BDF’s trajectory, including its key topics, institutional approach, and the involvement of both state and non-state actors. Furthermore, this paper will investigate to what extent the BDF supports the improvement of Indonesia’s democracy and how it positions Indonesia on the regional and global stage. This research will employ a qualitative method, drawing secondary data sources. Secondary data will be collected from the documents available on the official website of BDF, academic journals, and online news media. Ultimately, this paper aims to provide an analysis of whether the BDF is merely a normative agenda or whether it contributes substantial values to Indonesia’s democratic principles and beyond. Given the argument that democracy is declining in many parts of the world, it is worth discussing the trajectory of Indonesia’s democracy, particularly within the context of the BDF. This paper found that the value of Indonesia is being promoted through BDF, including Bhinneka Tunggal Ika, or Unity in Diversity; tolerance and harmony; as well as emphasizing the importance of dialogue in this Forum, without forcing any specific democratic system. Albeit its leadership in promoting democracy is being recognized, challenges and criticism towards BDF remain.